Long-term trends in English general practice consultation rates from 1995 to 2021: a retrospective analysis of two electronic health records databases - Tom Marshall; Mohammed A Mohammed; Steven Wyatt; Lyvia de Dumast (BMJ Open)
Objectives Although primary care is central to healthcare provision, inconsistent methods and data sources mean that relatively little is known about long-term trends in general practice consultation rates. We aimed to explore long-term trends in English general practice consultation rates using two electronic health records databases, Clinical Practice Research Datalink Gold and Aurum, from 1995 to 2021.Methods Consultations were identified and classified using a set of rules and code lists. Consultation rates were calculated as the ratio of the count of consultations and the registration duration. We used negative binomial regression to model the relationship between the number of consultations and the patient’s age, sex and year from each database. These models are then used to estimate annual crude consultation rates for England.Results The number of general practices in the Gold database decreased from 346 (1995) to 41 (2021), while in Aurum, it increased from 555 (1995) to 1347 (2021). In Gold, the average number of consultations per person-year increased from 2.91 in 1995 to 5.12 in 2012, then fell to 4.59 in 2019 and to 4.12 in 2021. In Aurum, average consultations per person-year rose from 2.17 (1995) to 4.89 (2012), then fell to 4.76 (2019) and rose again to 5.40 (2021). Half of the total increase in consultations from Aurum was due to a new consultation code, for ‘AccurX consultations’, an electronic messaging system for communication with patients.Conclusion Trends in general practice consultation showed three distinct epochs: rising from 1995 to 2012, falling from 2012 to 2019 and rising in Aurum but falling in Gold from 2019 to 2021. Consultation rates in Gold were higher than Aurum until the inclusion of a new consultation code in Aurum in 2019, which underscores the need for operational definitions of a consultation.